Pancasila dalam Konteks Kenegaraan Republik Indonesia: Sebuah Kerangka Konseptual - Ma'ruf, Aceng Muhammad Mahfud; Rahmat, Hayatul Khairul (PT Hakhara Akademia Indonesia, 2023)
Pancasila is the foundation and basis of the Indonesian state which regulates the entire constitutional structure of the Republic of Indonesia. In this position, Pancasila is a source of values and a source of norms in every aspect of state administration, including as a source of law and order in the Unitary State of the Republic of Indonesia. All laws and regulations and their elaboration are based on the values contained in the precepts of Pancasila. Therefore, the purpose of this paper is to (a) describe the meaning of Pancasila in the context of the state administration of the Republic of Indonesia, (b) the position of Pancasila in the state administration of the Republic of Indonesia, (c) the dynamics of the implementation of Pancasila in the state administration of the Republic of Indonesia, and (d) the role of Pancasila in the context of the state administration of the Republic of Indonesia. This writing uses library research methods. The results of this study are the 1945 Constitution is the state constitution of the Republic of Indonesia which was ratified as the state constitution by PPKI on August 18, 1945. Prior to the amendment or amendment to the 1945 Constitution, what is meant by the 1945 Constitution is the entire text consisting of 3 parts. namely the Preamble, the Body (consisting of 16 Chapters, 37 Articles, 4 Articles of Transitional Rules, and 2 Paragraphs of Supplementary Rules) and the Elucidation of the 1945 Constitution (which is divided into General Explanations and Explanations of Article by Article). In the period 1999-2002, the 1945 Constitution was amended 4 times. After the amendment, the 1945 Constitution was systematically changed. The systematics of the 1945 Constitution after the amendment consisted of the Preamble and the Articles (consisting of 37 Articles, plus 3 Articles of Transitional Rules and 2 Articles of Supplementary Rules).